Teologi Islam dalam Pandangan Jabariyah, Qodariyah, Mu'tazilah - Muhamad Abdul Latif (Jurnal Studi Islam dan Kemuhammadiyahan, 2023)
Discussion of the theology of divinity is the most important thing in Islam. This is very important because it involves aqidah for a Muslim and has a role in the formation of kaffah Muslim personalities. The purpose of this discussion is to describe the basics of thought of the jabariyah, qodariyah, and mu'tazilah groups. This research is a library research or literature review. The results of this study are that theology has many dimensions of understanding, but in general, theology is a science that discusses the facts and symptoms of religion and hostility to the relationship between God and humans, either by investigation or by pure reasoning, or by way of revelation. The third group has fundamental differences related to the form of Allah, Muhammad's apostleship, and the qur'an.